HPTLC Method Development and Validation for Determination of Rutin in Flavanoidal Fraction of Hibiscus micranthus Linn. - K. Ashok Kumar; S. Ramachandra Shetty; Laxmi Narasu (E-Journal of Chemistry)
A simple, precise and accurate high-performance thin-layer chromatographic method has been established for the determination of rutin in the stem extract of Hibiscus micranthus Linn. A flavonoid fraction of methanolic extract of the stem powder was used for the experimental work. Separation was performed on silica gel 60 F254 HPTLC plates with n-butanol: acetic acid: water: ammonia 3:1:1:1(v/v), as mobile phase. The determination was carried out using the densitometric absorbance mode at 286 nm. Rutin response was linear over the range 50–400 ng/μL. The concentration of rutin in the flavanoidal fraction was found to be 9.93%. The HPTLC method was evaluated in terms of sensitivity, accuracy, precision and reproducibility.